27 Therapeutic role of pelvic and para-aortic lymphadenectomy in apparent early stage epithelial ovarian cancer. (13th November 2020) - Bizzarri, N; Du Bois, A; Fruscio, R; De Felice, F; De Iaco, P; Casarin, J; Vizza, E; Chiantera, V; Corrado, G; Cianci, S; Harter, P; Ataseven, B; et al.
Abstract : Introduction: The therapeutic role of pelvic and para-aortic lymphadenectomy in surgical staging of apparent early-stage epithelial ovarian cancer (aeEOC) is still unclear. Recently, ESGO-ESMO consensus established that re-staging lymphadenectomy is not recommended if patients are already due to receive adjuvant chemotherapy for high-risk eEOC. The aim of this study was to evaluate the potential therapeutic role of systematic lymphadenectomy in patients with eEOC. Methods: Multi-center retrospective cohort study with CE approval, comparing women with aeEOC who underwent no lymphadenectomy (NL) versus lymph node sampling (SL) versus adequate systematic bilateral pelvic and para-aortic lymphadenectomy (AL) (defined as ≥20 lymph-nodes). Inclusion criteria: epithelial ovarian carcinoma; no bulky (≥10 mm short axis) pelvic or para-aortic lymph nodes at CT-scan; complete intra-peritoneal staging and at least 3 cycles of platinum-based adjuvant chemotherapy. Results: 639 of 2, 559 patients with FIGO stage IA-IIIA1 ovarian cancer, met inclusion criteria. 360 (56.3%) underwent AL, 150 (23.5%) SL and 129 (20.2%) NL (table 1 ). AL patients were younger (p<0.001), experienced a higher number of grade 3–5 post-operative complications (p=0.008) and had a longer time to start chemotherapy (p=0.034). There was no difference in intra-operative complications. Median follow-up was 63 months (range, 5–342). The 5-year disease-free survival (DFS) was 79.7% vs. 76.5% vs. 68.3% (p=0.006) (figure 1 ), and 5-year overall survival (OS) was 92.3% vs. 94.5% vs. 89.8% (p=0.165) (figure 2 ) in women who received AL vs. SL vs. NL, respectively. Lymphadenectomy represented independent factor for DFS improvement, HR 0.52 (95%CI 0.37–0.73) (p<0.001). Conclusion: Pelvic and para-aortic lymphadenectomy in surgical staging of eEOC improves DFS for the price of increasing post-operative complications and time to chemotherapy but does not affect OS.